FREQUENCY OF GUILLIAN-BARRE SYNDROME AND ITS VARIANTS AT MILITARY HOSPITAL RAWALPINDI - Awan, Marriam Hussain; Fazal, Imran; Lodhi, Muhammad Wajahat Alam; Anwer, Ayesha; Azhar, Rimsha; Qureshi, Muhammad Waleed Hassan (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the frequency, variants, clinical profile and outcome of patients admitted with the diagnosis of GuillianBarre Syndrome at neurology unit of a tertiary care teaching hospital of Pakistan.Study Design: Cross-sectional study.Place and Duration of Study: Neurology department, Pak Emirates Military Hospital Rawalpindi, from Jan to Dec 2018.Methodology: This study was conducted on 42 patients of Guillian-Barre Syndrome admitted in hospital. Demographic profile included age, gender, and the symptoms with which the patient presented. Medical and neurological complications were also documented among the target population. Outcomes included recovery, shifting to intensive care unit and death.Results: Out of 42 patients included in the final analysis 25 were male and 17 were female. Most of the patients presented with lower limb weakness followed by numbness. Acute inflammatory demyelinating polyneuropathy was the commonest while cranial nerve variant was least reported. Motor deficit were the commonest complication faced by the patients followed by respiratory involvement. Out of 42 patients, 34 (80.9%) recovered, 4 (9.5%) were shifted to the intensive care unit and 4 (9.5%) died.Conclusion: This study gives an insight into the pattern of a fairly common neurological illness which if diagnosed and managed in time has a good outcome in our set up. Management of critically ill Guillian-Barre Syndrome patients involves a multidisciplinary team with a need of intensive care unit during the course of management. Variety of types and presentations should be part of training of neurology doctors as well as internal medicine doctors.